Somatic growth and age of selected commercial fish species of the Cullera Coast, Iberian Peninsula, south-east Spain - Jaramillo-Londono, Angela Maria; Volpedo, Alejandra Vanina; Diaz-Arevalo, Jose Luis; Rodrigo-Santamalia, Maria Eugenia; Bendito-Dura, Vicent (Indian Journal of Fisheries, 2019)
This work provides data on the somatic growth and age of selected commercial fish species of the Cullera Coast, Spain. The biological information available that permits responsible fishing management of these species is relatively scarce. This study was conducted in the Bay of Cullera, Spain (39º 12’to 38º 59’N, and 0º 09’to 0º 15’W); and  selected benthic fish species were analysed that are frequently fished by trammel nets (mesh size 28-76 mm) at a maximum depth of 30 m. Maturity , age and growth of 63 torpedoes, Torpedo torpedo (L., 1758), 115 red scorpionfish, Scorpaena scrofa Linnaeus, 1758, 280 red mullets, Mullus surmuletus Linnaeus, 1758, 139 stargazers, Uranoscopus scaber Linnaeus, 1758, and 476 Portuguese soles, Dagetichthys lusitanicus de Brito Capello, 1868 were analysed. The data obtained in this study revealed that 50% of individuals of all the species reached sexual maturity at a TL (total length) of 20.0-36.5 cm and at an age of 2-6 years. The von Bertalanffy growth equation derived were: TL=37.0 (1 - e(-0.2(t + 0.33))); TL =31.5(1 - e(-0.38(t + 0.54))); TL =35.5(1 - e(-0.2(t + 2.08))); and TL =34.3(1 - e(-0.14(t + 2.16))) for S. scrofa, M. surmuletus; U. scaber  and      D. lusitanicus respectively. Keywords: Age, Commercial fish, Dagetichthys lusitanicus, Growth, Mullus surmuletus, Scorpaena scrofa, Torpedo torpedo, Uranoscopus scaber